Psychometric properties of Snijders- Omen test to measure non- verbal intelligence according to item response theory- on a sample of secondary school students in the city of Makkah - Alzahrani, Abdulrahman Jmman (Journal of Educational and Psychological Sciences, 2022)
The current study aimed at creating Psychometric characteristics to test Sinjders- Oomen to measure non- verbal intelligence, and find criteria for explanation of ability to individuals, and the classified approach was used in Sinjders- Oomen. A secondary school in Makkah city, the results showed that the most appropriate data model is Two- Parameter Model, after ensuring the assumptions of Item Response Theory for the examination of the study data, and are Unidimensional using the Nonparametric factor analysis method T= 2.13 "For a stout method at the level of significance (P = 0.016), a statistically function, It explains that only one latent variable is sufficient to explain the variance of individuals' performance on the test. The paragraph analysis method was used using noharm3 software and the value of the square root index for the average boxes (RMSR = 0.007) was very close to scratch. The value of the Tanaka Index for Good Match (0.977) is very close one in the correct one, and the values ​​point to Goodness of fit to the Unidimensional model. The method of detection of local independence was used for paragraphs Yen Q3, and the appropriateness of individuals and paragraphs for the Two- parameter Logistic. The results confirmed that the test paragraphs included a wide range of difficulty and tend to graduate at the difficult level and that the average normative mistakes of the difficulty of the difficulty of the difficulty (0.151) is a standard deviation (1.949), small values ​​indicated that values ​​were highly appreciated, as well as a function Test information in the light of the item response theory for the separation of the organs, the capacity of individuals (θ) has also been found for the corresponding to each degree of crude college on the test, and the standards explained in the performance of the performance on the test. Based on the results presented several recommendations and proposals:1- Provide the opportunity for graduate students in measurement and evaluation for the exact details of item response theory.2- Pay attention to the training of graduate students during systematic study on the use of existing response theoretical applications and applying what has been studied at the theoretical side.3- Use the models of response to the disruption of the tests and psychological standards.4- Restructuring psychological tests in the light of the models of response for the disruption.The researcher also recommends the use of Sinjders- Oomen test or sealing the students with higher mental abilities in the Ministry of Education to detect talented intelligence in talented care centers. As well as in care centers for intelligence of deaf and mute and mutual disabilities and autism.
Keywords: Sinjders; Oomen test; Sinjders- Oomen test; non- verbal intelligence; psychometric properties; Item response theory; Two- parameter Logistic model